Crohn's and colitis for dummies - Ali, Tauseef (--For dummies., 2013)
Crohn's disease and ulcerative colitis are often debilitating diseases that have life-altering impacts on sufferers. This guide help you to actively recognize the symptoms, and explains in plain English the consequences you'll face if the diseases go untreated.